HUBUNGAN KEBIASAAN CUCI TANGAN DENGAN KEJADIAN CACINGAN PADA ANAK USIA SEKOLAH DI SD NEGERI BLINDUNGAN IV KABUPATEN BONDOWOSO - Yuyun Triwahyuni; Lulut Sasmito; Lailil fatkhuriyah (Jurnal Kesehatan dr. Soebandi, 2016)
Worm disease can infect all age groups, but the highest prevalence is in the elementary school age group. If seen the long-term effects of helminthiasis cause significant losses in patients. This study aims to determine how handwashing habits affect the incidence of intestinal worms in school-age children in SD Blindungan 4, Bondowoso Regency in 2014. This study uses a descriptive correlative research method of 46 samples. Handwashing habits practiced by school-age children in Blindung 4 Elementary School in Bondowoso Regency are rarely conducted so that it becomes one of the factors in the occurrence of intestinal worms. With a percentage level of rarely washing hands as much as 58.7%. The incidence of intestinal worms in SD Blindugan 4 Bondowoso Regency from the results of the laboratory examination found that there were still many students in SD Blindung 4 suffering from intestinal worms with a percentage of 56.5% with positive results. Data analysis using Chi Square test. There is a relationship between handwashing habits with the incidence of intestinal worms in school-age children in SD Blindungan 4, Bondowoso Regency. Worms occur frequently in children who rarely wash their hands before eating, after playing and after defecation. So from the results of the study it can be concluded that all children who need to wash their hands before eating, after playing and after defecation there are still infected with intestinal worms, whereas in children who rarely do the habit of washing hands before eating, after playing and after defecating the incidence is more . For this reason, counseling on hand-washing with school-age children is needed as one of the prevention of intestinal worms and the provision of facilities to wash hands in schools